Finite-time stability of a class of nonautonomous systems. Issue 10 (3rd October 2022) - Li, Mengqin; Jiang, Minghui; Ren, Fengmin; Zhang, Yadan
Abstract : In this paper, the finite-time stability of nonautonomous systems is studied by using Lyapunov Krasovskii method and Gronwall inequality. Firstly, a new lemma for the finite-time stability for nonautonomous systems is given by using Gronwall inequality. which make the derivative of Lyapunov function not to be negative all the time. Then, based on the new lemma and Lyapunov Krasovskii method, some finite-time stability criteria about nonautonomous linear systems and nonlinear systems are proposed. Based on this, by designing controllers, the finite-time stabilizable theorem is obtained. In addition, it is pointed out that the conclusion of this paper is more general than the existing literature in the remarks. Finally, several examples are simulated with MATLAB to verify the effectiveness of the results.